The perception of a foreign language (korean) and speech achievement of competence model of graduate translator - Ten, Yu P (Journal of Oriental Studies, 2016)
The present article studies the perception of the Korean speech and pronunciation, and the ability to use varying Korean language communication tools in accordance with different situations.